2020
DOI: 10.1101/2020.12.21.423733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of a dysregulated Vitamin D pathway in SARS-CoV-2 infected patient’s lung cells

Abstract: Although a defective vitamin D pathway has been widely suspected to be associated in SARS-CoV-2 pathobiology, the status of the vitamin D pathway and vitamin D-modulated genes in lung cells of patients infected with SARS-CoV-2 remains unknown. To understand the significance of the vitamin D pathway in SARS-CoV-2 pathobiology, computational approaches were applied to transcriptomic datasets from bronchoalveolar lavage fluid (BALF) cells of such patients or healthy individuals. Levels of vitamin D receptor, reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Molecular expression of CYP27A1 and FGFR1 were remained low. Increased expression of CYP24A1 were found when the core Vitamin D receptor molecules were analysed, for coalition of SARS-CoV-2 and Vitamin D receptors, in infected unsolidified bronchoalveolar lavage cells of RNA sequencing-based transcriptomic datasets, of human bronchial epithelial cells (NHBE), Non-small cell lung cancer cells (Calu3) and A549 Lung cell lines of human species [67]. The possible correlation between mitogen-activated protein kinase (PAK) and genes modulated by Vitamin D was observed.…”
Section: Immunomodulatory and Cellular Proliferation Of Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular expression of CYP27A1 and FGFR1 were remained low. Increased expression of CYP24A1 were found when the core Vitamin D receptor molecules were analysed, for coalition of SARS-CoV-2 and Vitamin D receptors, in infected unsolidified bronchoalveolar lavage cells of RNA sequencing-based transcriptomic datasets, of human bronchial epithelial cells (NHBE), Non-small cell lung cancer cells (Calu3) and A549 Lung cell lines of human species [67]. The possible correlation between mitogen-activated protein kinase (PAK) and genes modulated by Vitamin D was observed.…”
Section: Immunomodulatory and Cellular Proliferation Of Vitamin Dmentioning
confidence: 99%
“…These might have impact upon cytokine signalling, immune regulation and NF-kB pathway. The biotic properties of Vitamin D ensue by either genomic or non-genomic methods, which involves membrane associated rapid response steroid binding receptors (MARRS) and by up regulation and down regulation in expression of cellular genes which enkindle the depletion of Vitamin D expression pathway in infected lung cells of SARS-CoV-2 [67,68].…”
Section: Immunomodulatory and Cellular Proliferation Of Vitamin Dmentioning
confidence: 99%
“…Indeed, several studies suggest that Vit D 3 may have beneficial properties against SARS-CoV-2, as individuals deficient in Vit D 3 appear to be more susceptible to contracting the virus than those whose levels are normal ( Arvinte et al, 2020 ; Hernández et al, 2020 ; Kaufman et al, 2020 ; Radujkovic et al, 2020 ). Additionally, reduced levels of VREs (important in AMP induction ( McMahon et al, 2011 ; Aguilar-Jimenez et al, 2013 )) in cells isolated from bronchoalveolar lavage were found in patients infected with CoV-2 than healthy subjects ( George et al, 2020 ). Moreover, the fact that LL-37 ( Zhang et al, 2020 ) and hBD-2 ( Zhang L. et al, 2021 ), both regulated through Vit D 3 , were able to block S protein–expressing pseudovirions from infecting vulnerable human cells supports the notion that healthy levels of Vit D 3 may be important in reducing the risk of acquiring SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%